THE USE OF DIGITAL TECHNOLOGIES TO PREPARE FUTURE TRANSLATORS - Khamidov Bekhruz Ziyot ugli (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  The  integration  of  digital  technologies  in  translator  education  is essential  for  equipping  future  professionals  with  the  skills  needed  to  navigate  the evolving  translation  landscape.  This  study  explores  the  role  of  computer-assisted translation (CAT) tools, artificial intelligence (AI) applications, and virtual exchange programs  in  enhancing  translator  training.  It  examines  both  the  benefits  and challenges  of  incorporating  these  technologies  into  educational  programs  and assesses their impact on students' professional preparedness. The findings underscore the importance of digital literacy, adaptive learning, and industry-aligned curricula in developing competent, technology-savvy translators ready to meet the demands of a rapidly changing industry.